Hubungan Dukungan Suami pada Ibu Pasca Melahirkan dengan Postpartum Blues - Nurhayati, Nung Ati (Syntax Idea, 2021)
This study aims to get an overview of "Husband Support Relationship in Postpartum Mothers with Postpartum Blues in Polyclinic KIA/KB RS. DustiraCimahi" research is a descriptive correlation of collecting data cross-sectionally. Samples were taken by acsidental sampling as many as 40 mothers after giving birth to the early postpartum phase (days 3-10). Questionnaires for husband support compiled by researchers refer to the theory according to Murtiningsih, (2012) validity test results from 24 questions there are 4 invalid questions, 2 questions discarded 2 questions corrected, so that the question used as many as 22 items. Questionnaire for postpartum blues using EPDS with assessment criteria 0-9 not postpartum blues 10-30 postpartum blues. The results showed that of the 40 respondents almost half felt they did not get support from their husbands and almost half had postpartum blues. Statistical test results obtained p value = 0.000 then concluded there is a significant relationship between husband support and postpartum blues events. The results of the analysis showed OR = 77,000 means that if the husband is perceived not to support his wife then his wife has a risk of 77 times will experience postpartum blues compared to the husband who is perceived to support his wife. Advice, for nurses should provide education and counseling about postpartum blues by involving the family to the mother from pregnancy until the time of returning postpartum care. For hospitals, it is expected to make SOP about early detection of postpartum blues and nursing care and socialize to all nursing personnel who are in the room and polyclinic midwifery.